Grade Inflation: Analatical Study About the Grades of Shaqra University Students - Nayel O. Al Kaabnh (Sultan Qaboos University, 2018)
This study aimed at defining  grade inflation among  Shaqra University students. A number of 819 randomly chosen grade records of Shaqra University students enrolled between 2010- 2015, were analyzed. The results show the average of students who get high grades (including A+, A, B+) according to the grading system of the university. Meanwhile, the results show a decrease in the average number of students who got the grades B, C+. It has been also noticed that the average of the student who got the grades C, D+, D increased, whereas the average of those who got F decreased.The results of this study have shown also that the successional deviation for the percentage average of the students who got these grades A+, A, B+, B, C, D+, D, was positive, and negative for grades B, C+, F for the same period. Moreover, the results have shown a significant difference of (α=0.05)  for students who got these grades A+, A, B+, B, C+, D+, F. This lead to conclude that the percentage average for students getting high grades increase respectively resulted in grades inflation.